MENINGKATKAN MOTORIK HALUS MELALUI KEGIATAN MEWARNAI PADA ANAK USIA 5-6 TAHUN - Rumsiah, Eneng Sri Susilawati, Suci Aprilyati Ruiyat (JURNAL PENDIDIKAN DAN PENELITIAN SERUMPUN MENGAJAR, 2024)
The purpose of this study was to improve fine motor skills through coloring activities at PAUD Azzuhairo Jawilan. Fine motor skills are very important to support the next level of education. Classroom action research was conducted in 2 cycles. This study consisted of 10 children in group B PAUD Azzuhairo with the object of fine motor skills. Data collection used was observation and documentation. Data analysis used quantitative and qualitative descriptive. The results of observations of fine motor skills before the action averaged 36.25% with MB criteria, an increase of 57.5% in cycle I with BSH criteria, and an increase of 88.12% in cycle II with BSB criteria. Based on the data, it can be concluded that children's fine motor skills have increased and achieved success indicators.